Sýntomē Historía tē͂s Apokalyptikē͂s Kinḗseōs kaì Grammateías - Tilly, Michael 1963- (2014)
In this article, the following issues will be addressed: a) roots and origin of Apocalypticism in the Ancient Judaism, b) apocalyptic interpretations of the world through the centuries, and c) Apocalypticism and Modern Culture.